In-hospital free fatty acids levels predict the severity of myocardial ischemia of acute coronary syndrome. Issue 1 (December 2016) - Ma, Pei; Han, Lu; Lv, Zhihua; Chen, Wei; Hu, Hanning; Tu, Jiancheng; Zhou, Xin; Liu, Song-Mei
Abstract Background We aimed to assess whether the levels of FFAs (free fatty acids) in ACS (acute coronary syndrome) patients depend on the extent of myocardial ischemia during the subacute phase of ACS attack. Methods A total of 892 consecutive CAD (coronary artery disease) subjects undergoing coronary angiography were enrolled. The FFAs contents were measured based on enzymatic assay. The relationship between FFAs and Gensini score and ACS susceptibility was assessed. Results In the overall population, the upper FFAs quartile was accompanied with higher ischemia parameters and increased occurrence of ACS and STEMI (ST-segment elevation myocardial infarction) (P < 0.05). The FFAs concentrations were approximately 1.5-fold higher in ACS than in stable CAD patients, roughly 1.3-fold higher in STEMI than non-STEMI ACS patients and probably 1.3-fold higher in non-STEMI ACS than in stable CAD patients. After adjusted for traditional cardiovascular risk factors, the FFAs level remained a risk factor for a higher Gensini score with more than 40 (P < 0.001) and prevalent ACS (P < 0.001). After adjusted for traditional risk factors, FFAs levels after natural logarithm transformation were associated with hs-CRP and WBC counts in ACS patients. A multiplicative interaction was found between hs-CRP, WBC counts and FFAs in incident ACS and higher Gensini score (P < 0.001). Conclusions Higher in-hospital levels of FFAs persist and may reflect the severity of ischemia and necrosis during the subacute phase of ACS attack.